Therapy process in migration circumstances (Round-Table Discussion) - Anna Varga; Marina Travkova; Irina Znamenskaya (Психология и Психотерапия Семьи)
The recent events have made migration a routine and online sessions a part of our everyday life. Though many challeges arise along with this. How does therapy itself change when the client and therapist are on either side of the divide? What happens to marriages that become commuter, although they did not plan it? How do we deal with the cultural shock that befalls our clients? The participants of the roundtable discussion, which took place on November 8, 2024, talked about changes in the client-therapeutic interaction and the therapy itself in the current conditions, and tried to find answers to important questions.